Exchange Rate Economics - Williamson, John (World Bank, Washington, DC, 2017)
Much of the paper is devoted to expounding the standard model of the exchange rate accepted by most economists today. This regards the exchange rate as a forward-looking asset price. Its steady-state level is determined by the need to have a current account balance that will keep the debt/gross domestic product (GDP) ratio constant, while the path of adjustment toward this steady-state level is determined by the representative agent's rational expectation of what will happen between now and the long run. The paper then examines a number of criticisms of this model: that exchange rate changes are driven by 'news' and will be nonexistent in the absence of news; that it implies that chartist rules will systematically lose money; and that it leaves no room for 'bubble-and-crash' dynamics, which appear to have occurred. An alternative 'behavioral' model that gives room for such behavior is presented. The paper then argues that overvaluation can thwart development through an attack of 'Dutch disease,' and discusses the role that exchange rate policy may play in avoiding this outcome. This demands primarily the use of nonmonetary instruments like fiscal policy or capital controls, but the behavioral model of the exchange rate implies that intervention can also play a role. The paper also includes a discussion of the alternative exchange-rate regimes available.